Pengaruh Kompensasi dan Beban Kerja Terhadap Intention to Quit Karyawan dengan Produktivitas Sebagai Variabel Intervening pada PT. Arta Boga Cemerlang: Unit Depo Medan - Anggi Ardiansyah; Iskandarini; Anizar Anizar (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the effects of compensation and workload on employees' intention to quit, with productivity as an intervening variable, at PT. Arta Boga Cemerlang (Medan Unit). A quantitative method was employed, collecting data via questionnaires distributed to 56 respondents. Data were analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results indicate that compensation has a significant negative effect on intention to quit, while workload has a significant positive effect. Employee productivity was found to mediate the relationship between compensation and intention to quit, as well as between workload and intention to quit. This research provides practical recommendations for company management to effectively manage compensation and workload to enhance productivity and reduce employee intention to quit levels.